Efficacy and safety of Osteoking on fracture healing: a systematic review and meta-analysis - Zhang, Le; Kuang, Haomin; Zhang, Zimin; Rong, Kuan; Yuan, Yiwei; Peng, Zhifei; Zhao, Haomin; Liu, Ke; Ou, Liang; Kuang, Jianjun (Frontiers in Pharmacology, 2024)
Background: Osteoking (OK) is prescribed in traditional Chinese medicine to accelerate fracture healing. Although some studies suggest the potential efficacy of OK for fracture healing, the evidence remains inconclusive.To systematically evaluate the safety of OK and its effect on fracture healing.Methods: Relevant authoritative databases were searched until August 25, 2023. Randomized controlled trials (RCTs) of patients with fractures treated with Osteoking were included. We evaluated the risk of bias using the Cochrane tool and performed a meta-analysis using the Review Manager 5.4 software package.Results: 13 studies involving 1123 participants were included. This metaanalysis showed that compared with observations in the control group, the OK group showed a shortened fracture healing time, increased fracture healing rate, reduced swelling regression time and ecchymosis regression time, and improved bone metabolism. In addition, the included studies did not report any serious side effects associated with the use of OK, and the mild side effects resolved without treatment.Conclusions: OK therapy is beneficial and safe for accelerating fracture healing, reducing swelling, eliminating ecchymosis, and improving bone metabolism. However, the meta-analysis results do not support OK treatment for improving the fracture healing rate and reducing pain across all fracture sites. Further original, high-quality studies are needed to validate these findings.